Wave interference and band gap control in multiconductor one-dimensional Bragg structures - Konoplev, I; McGrane, P; Cross, A; Ronald, K; Phelps, A (2005)
A theoretical study of scattering and interference of waves in one-dimensional (1D) Bragg structures, also known as photonic band-gap (PBG) structures, based on multiconductor waveguides is presented. The case of small perturbations of the waveguide walls was analyzed. Using the coupled-wave theory the expression for the wave-coupling coefficient was generalized. The possibility of controlling the scattered wave polarization and the band gap locations in such structures due to the constructive and destructive interference of the waves was demonstrated. It was shown that such control can be achieved by adjusting the relative phase of the 1D periodic perturbations with respect to each other. As an example a 1D structure based on a coaxial waveguide was studied using three-dimensional computer simulations and coupled-wave theory. The dispersion diagrams are presented and the dependence of the reflected wave structure on the phase between the corrugations analyzed and discussed. To demonstrate the validity of the theory the results obtained for the basic coaxial model with a single corrugated conductor are compared with the experimental results observed. © 2005 American Institute of Physics.